Heteromeric glycolipid complexes as modulators of autoantibody and lectin binding. - Rinaldi, S; Brennan, K; Willison, H (2010)
Glycolipids act as receptors for a wide range of antibodies, lectins and microbes. It has long been recognised that the local topography of glycolipids in the plasma membrane is critical to these recognition events, although the biological basis for this has been relatively under-investigated. Within the last five years, emerging evidence indicates that hetero-dimeric clusters of different glycolipids can form highly distinct and specific epitopes for antibody and lectin binding. The initial observation that these ganglioside complexes (GSC) could either dramatically enhance or equally well inhibit the binding of neuropathy sera has now been reproduced for a number of other lectins, including siglecs and bacterial toxins. Here we review the initial discovery of GSC as antibody binding domains and the subsequent studies delineating their broader functional importance. Potential mechanisms underlying these effects are considered, although much remains to be investigated and explained. However, the implications for this field are potentially widespread, ranging from glycoarray design, structural biology and membrane biophysics, through to the biological consequences of glycolipid complex organisation in plasma membranes.